Alumni-based activities - UiTM, Faculty of Business and Management (UiTM, 2021)
The alumni-based activities in 2021 focused on student support and engagement initiatives, including the “1 Alumni 1 Computer” programme and the Alumni Talk series. These activities strengthened alumni–student connections while enhancing learning support and career exposure.